2009
DOI: 10.1080/10428190802517740
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system infections in immunocompromised patients – update on diagnostics and therapy

Abstract: Infections of the central nervous system (CNS) are increasingly reported in patients with malignancies. Heavily immunocompromised patients like those after allogeneic stem cell transplantation (SCT) or previous T cell depleting treatment regimens (e.g. with fludarabine or alemtuzumab) are at highest risk for cerebral infections. The spectrum of causative organisms may vary greatly, depending on the underlying malignancy, its treatment and various other factors. Toxoplasma gondii and fungi are the leading causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 108 publications
1
37
0
1
Order By: Relevance
“…The Infectious Diseases Society of America (IDSA) guidelines do not recommend the use of any antiviral agent to treat EBV encephalitis, albeit other authors suggested that acyclovir or ganciclovir might be useful. 10,12,34 However, further investigations are required to draw definite conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Infectious Diseases Society of America (IDSA) guidelines do not recommend the use of any antiviral agent to treat EBV encephalitis, albeit other authors suggested that acyclovir or ganciclovir might be useful. 10,12,34 However, further investigations are required to draw definite conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Eligibility criteria included previous allo-SCT, a positive CSF virus PCR and neurological symptoms that were not entirely attributable to conditions other than viral encephalitis. [8][9][10][11][12][13][14][15][16][17][18]20,23,24 To minimize underreporting, eligible patients were identified whenever possible from an electronic database that was supplied by the affiliated departments of virology recording all positive CSF PCR findings of the respective transplant center. Relevant data were collected on standardized case report forms by a member of the coordinating center (J. Schwender, Charité Campus Benjamin Franklin, Berlin, Germany) together with a member of the respective participating center.…”
Section: Patients Study Design and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 There are several risk factors for CNS infection in these individuals, depending on the underlying malignancy, its treatment and various other factors. Among causative organisms, Toxoplasma gondii is the most prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…4,26 Prophylactic therapy is an important factor in toxoplasmosis prevention. In immunocompromised patients with high risk of reactivation of a latent T. gondii infection (eg.…”
Section: Discussionmentioning
confidence: 99%